Intermittent screening and treatment for malaria complementary to routine immunisation in the first year of life in Papua, Indonesia: a cluster randomised superiority trial - Poespoprodjo, JR; Hafiidhaturrahmah; Sariyanti, N; Indrawanti, R; McLean, ARD; Simpson, JA; Kenangalem, E; Burdam, FH; Noviyanti, R; Trianty, L; Fadhilah, C; Soenarto, Y; et al. (BioMed Central, 2022)
Background In Papua (Indonesia), infants with P. falciparum and/or P. vivax malaria are at risk of severe anaemia and death. We hypothesized that in an area of high malaria transmission, intermittent screening and treatment of infants with malaria (ISTi) will reduce morbidity compared to passive case detection (PCDi). Methods We conducted a cluster randomised, open label, superiority trial. A total of 21 clusters of village health posts (VHP) were randomised 1:1 to either IST for infants coinciding with 4 routine immunisation visits or PCDi. Healthy term infants born to consenting mothers enrolled into a maternal malaria cluster randomised trial were included in the study and followed for 12 months. Point of care malaria rapid diagnostic tests were used to detect peripheral parasitaemia at 2, 3, 4 and 9 months old in all infants in ISTi clusters and when symptomatic in PCDi clusters. Infants with detected peripheral parasitaemia were treated with dihydroartemisinin-piperaquine. The co-primary outcomes were the incidence rate of clinical malaria in the first year of life and the prevalence of parasitaemia at age 12 months. The incidence rate ratio and prevalence ratio between ISTi and PCDi were estimated using mixed-effects Poisson and log-binomial regression modelling (accounting for clustering at VHP level). Results Between May 2014 and February 2017, 757 infants were enrolled into the study, 313 into 10 ISTi clusters, and 444 into 11 PCDi clusters. Overall, 132 episodes of parasitaemia were detected, of whom 17 (12.9%) were in symptomatic infants. Over 12 months, the incidence rate (IR) of clinical malaria was 24 [95% CI, 10–50] per 1000 children-years at risk in the ISTi arm and 19 [95% CI, 8,38] per 1000 children-years in the PCDi arm (adjusted incidence rate ratio [aIRR] 1.77 [95% CI, 0.62–5.01]; p = 0.280). The prevalence of parasitaemia at 12 months was 13% (33/254) in the IST clusters and 15% (57/379) in the PCD clusters (adjusted prevalence ratio (aPR) = 0.92 (95% CI, 0.70–1.21), p = 0.55). There was no difference in the risk of anaemia between treatment arms. Conclusions In high malaria transmission area outside of Africa, our study suggests that compared to PCDi, ISTi offers no significant benefit in reducing the risk of clinical malaria in infants born to women receiving effective protection from malaria during pregnancy. Trial registration ClinicalTrials.gov NCT 02001428, registered on 20 Nov 2013.